Frequency and parasite load in gills of cachama fry (Colossoma macropomum) through direct examinations in three fish farms in Ucayali, Peru - Rondón E., Juan (2021)
The aim of this study was to determine the frequency and load of ectoparasites in gills of cachama fry from three semi-intensive farming fish farms in the province of Coronel Portillo, Ucayali, Peru. Sixty fingerlings (35-45 days old) were selected from each of the three fingerling supply establishments (E1, E2 and E3), reared at similar density and feeding conditions. Three fresh gill layer sections were evaluated from both sides, by visual observation with a 2x magnifying glass to detect crustaceans and by direct microscopy at 10x for trematodes and at 40x for protozoa. Four degrees of infestation were considered; null (0 parasites), mild (1-3), moderate (4-7) and severe (>8). It was possible to identify mainly forms compatible with monogeneans of the Dactylogyridae family, compatible with Dactylogyrus spp (41.1%) and protozoa, mostly of the Oodiniaceae family, compatible with Piscinodinium spp (10.6%). No crustaceans were found. The frequencies of infestations were 28.3, 86.7 and 18.3% in E1, E2 and E3, respectively. Parasitic loads were mostly light (87.5, 53.8 and 83.3% for monogeneans and 80, 70 and 100% for protozoa, in E1, E2, and E3, respectively). The results suggest a lower sanitary condition in the E2 fingerlings. It is concluded that there was a higher frequency of infestations by monogeneans and light parasite loads in gills of cachama fry from the three fish farms evaluated by direct examinations.